Radiofrequency Intensity Exposure Levels from the Digital Terrestrial Television (DTTV) Broadcasting Transmitter in Kampala Metropolitan; Uganda - Opio, Peter; Kisolo, Akisophel; Okullo, Willy; Ayugi, Gertrude; Muhereza, Bobrich Mwecumi; Ireeta, Tumps (Technium: Romanian Journal of Applied Sciences and Technology, 2021)
In this paper, we present the investigation in the radiofrequency intensity exposure levels from the DTTV broadcasting transmitters in, Nakulabye residential area, Mulago Hospital, Physics Department of Makerere University and Kyambogo Senior Secondary School, all in Kampala metropolitan. The DTTV frequency bands considered in this study were the sub 700MHz (474MHz-694MHz) and the 700 MHz (694 MHz-790 MHz) frequency bands. Investigation was done for three constant days in each of the Measurement Locations (MLos) using the Aaronia Spectran HF-6065 V4 spectrum analyzer, Aaronia AG HyperLOG 4025 Antenna, Aaronia GPS Logger, real time Aaronia MCS spectrum-analysis-software and a T430s Lenovo Laptop. In all these MLos, the mean daily and projected monthly exposure levels ranged from 0.00049 µW/m2/day to 0.002542 µW/m2/day and from 0.00495µW/m2/month to 0.02410 µW/m2/month in the sub 700 MHz frequency band while as in the 700 MHz frequency band, it ranged from 0.00076 µW/m2/day to 0.00209 µW/m2/day and from 0.00769 µW/m2/month to 0.07944 µW/m2/month. The results of this study show that the maximum exposure levels are very low when compared with the recommended International Commission on Non-Ionizing Radiation Protection (ICNIRP) safety RF intensity exposure level limits.